1999
DOI: 10.1002/(sici)1521-3773(19990517)38:10<1405::aid-anie1405>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of a Molecular Floral Lace with One-Dimensional Channels and Inclusion of Glucose

Abstract: A three-dimensional network with one-dimensional channels (see picture) has been self-assembled from the nickel(II) complex of cyclam and 1,3,5-benzenetricarboxylate in water through hydrogen-bond formation. The channels have an appropriate diameter (10.3 Å) to include D-glucose with a formation constant of K =(1.38±0.01)×10 M . Under similar conditions maltose is not included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(115 citation statements)
references
References 4 publications
3
111
0
1
Order By: Relevance
“…The structural factor, i.e., agreement of the pore size and geometrical parameters of the adsorbate is not a principal requirement in the adsorption of small monohydric alcohols but becomes predominant in interaction with large molecules. Thus, OMF derived from the macrocyclic nickel complex [Ni(cl)(H 2 O) 2 ] 3 (BTC) 2 ·24H 2 O (cl = 1,4,8,11-tetraazacyclotetradecane, cyclam, BTC 3-is the 1,3,5-benzenetricarboxylate anion) efficiently bind D-glucose but do not interact with maltose (glucose dimer) [8].The interaction of such framework materials with metal complex species has been studied much less extensively although we might expect high selectivity in systems of OMF adsorbents and metal complex adsorbates in light of the fit of the geometrical dimensions of the adsorbate and adsorbent pores and the complementary spatial nature of the reagents from the viewpoint of a chemical reaction between them. Furthermore, since the adsorbed metal complexes are in a molecularly dispersed state within the matrix, their subsequent transformations may lead to the formation of hybrid materials containing new types of nanoparticles or clusters in the OMF cavities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The structural factor, i.e., agreement of the pore size and geometrical parameters of the adsorbate is not a principal requirement in the adsorption of small monohydric alcohols but becomes predominant in interaction with large molecules. Thus, OMF derived from the macrocyclic nickel complex [Ni(cl)(H 2 O) 2 ] 3 (BTC) 2 ·24H 2 O (cl = 1,4,8,11-tetraazacyclotetradecane, cyclam, BTC 3-is the 1,3,5-benzenetricarboxylate anion) efficiently bind D-glucose but do not interact with maltose (glucose dimer) [8].The interaction of such framework materials with metal complex species has been studied much less extensively although we might expect high selectivity in systems of OMF adsorbents and metal complex adsorbates in light of the fit of the geometrical dimensions of the adsorbate and adsorbent pores and the complementary spatial nature of the reagents from the viewpoint of a chemical reaction between them. Furthermore, since the adsorbed metal complexes are in a molecularly dispersed state within the matrix, their subsequent transformations may lead to the formation of hybrid materials containing new types of nanoparticles or clusters in the OMF cavities.…”
mentioning
confidence: 99%
“…The structural factor, i.e., agreement of the pore size and geometrical parameters of the adsorbate is not a principal requirement in the adsorption of small monohydric alcohols but becomes predominant in interaction with large molecules. Thus, OMF derived from the macrocyclic nickel complex [Ni(cl)(H 2 O) 2 ] 3 (BTC) 2 ·24H 2 O (cl = 1,4,8,11-tetraazacyclotetradecane, cyclam, BTC 3-is the 1,3,5-benzenetricarboxylate anion) efficiently bind D-glucose but do not interact with maltose (glucose dimer) [8].…”
mentioning
confidence: 99%
“…Figure 2a shows the WMC structure of 1 as a periodic unit obtained by the X-ray crystal structure analysis at 293 K, which was previously reported by Suh and co-workers. 10 Moreover, Figure 2b shows the WMC structure of 2 obtained by immediately decreasing the temperature to 223 K, after it was exposed to air for 30 min at room temperature and coated with adhesives. Figure 2c also shows the WMC structure of 2 obtained at 223 K in a closed glass capillary under saturated humidity conditions after the melting point of 2.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to form a complete 1D nanoporous framework with a large pore size of >1 nm width by the self-assembly of some programmed building blocks with intermolecular H-bonding and coordination bonding interactions. Suh and co-workers 10 reported the synthesis of {[Ni II (cyclam)] 3 (TMA) 2 ¢24H 2 O} n (1) (TMA: trimesate, cyclam: 1,4,8,11-tetraazacyclotetradecane), which is a molecular crystal with a complete 1D nanoporous framework, using complementary intermolecular H-bonding interactions with molecular building blocks and as a template for 1D water molecular clusters (WMCs) in nanoporous channels. The previously reported X-ray crystal structure analysis of 1 at room temperature showed that the WMCs confined to the nanoporous channels of 1 had a nanotube-like structure with a 1D vacant space around the centre.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Hydrogen bonds play vital roles in highly efficient and specific biological reactions and are essential for molecular recognition and self-organization of molecules in supramolecular chemistry. The coordination environment of the metal is generally constrained by the macrocyclic ligand, so the metal may be considered to be an inert substituent on the hydrogen bonding organic fragment.…”
Section: Copper(ii) 25-pyridinedicarboxylate Introductionmentioning
confidence: 99%